TAUHID DAN ETIKA LINGKUNGAN: Telaah atas Pemikiran Ibn ‘Arabī - Ahmad Munji (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2014)
Abstract: Tauḥīd (monotheism) affirms that God has created man most excellent among the creatures with the aim to serve Him. Proof of service must be proved by maintaining the best possible environment as He wills. It will consequences which bring up the ethics that guide humans to interact with their environment. Therefore, the relationship of Tauḥīd and ethics as good and bad links or ethical character that relies heavily on clean and dirty soul and reflect the quality of faith (īmān) and Tauḥīd (monotheism) itself. This article aims to elaborate on the relationship of Tauḥīd with mindset, because the mindset is mental activity that requires imagination in many ways and requires a balance; Tauḥīd relationship with the pattern of attitudes; patterns of attitude is the basic concept of a person's behavior; relationship between Tauḥīd and behavioral patterns ('amal). 'Amal is a reflection of a very concrete. From this pattern can be described as follows: Tauḥīd produces ethics, and ethics produces behavior ('amal). The pattern of this relationship in real life can be seen, among other things, how human beings interact with other God’s creatures (environment). Abstrak: Tauḥīd menegaskan bahwa Tuhan telah menciptakan manusia yang paling baik di antara para makhluk dengan tujuan untuk mengabdi kepada-Nya. Bukti pengabdian harus dibuktikan dengan menjaga lingkungan sebaik-baiknya sebagaimana yang dikehendaki-Nya. Konsekuensi dari ini akan memunculkan etika yang memandu manusia dalam berinteraksi dengan lingkungannya. Sebab, hubungan Tauḥīd dan etika seperti keterkaitan baik dan buruknya akhlak atau etika yang sangat bergantung pada bersih dan kotornya jiwa dan mencerminkan kualitas dari iman dan tauhid itu sendiri. Artikel ini bertujuan mengelaborasi hubungan Tauḥīd dengan pola pikir, karena pola pikir adalah aktivitas jiwa yang memerlukan khayal dalam berbagai hal dan membutuhkan keseimbangan; hubungan Tauḥīd dengan pola sikap; pola sikap adalah konsep dasar dari sebuah perilaku seseorang; hubungan antara Tauḥīd dan pola perilaku (‘amal). ‘Amal merupakan cerminan yang sangat kongkrit. Dari sini pola ini dapat digambarkan sebagai berikut: Tauḥīd menghasilkan etika, dan etika menghasilkan perilaku (‘amal). Pola hubungan ini dalam kehidupan riil dapat dilihat, antara lain, bagaimana manusia berinteraksi dengan makhluk-makhluk Tuhan yang lain (lingkungan). Keywords: Tauḥīd, ‘amal, ethic, Ibn ‘Arabī, Allāh, enviromenment.